Uji Sitotoksisitas Nanopartikel Sisik Ikan Gurami (Osphronemus Gouramy) Terhadap Sel Fibroblas Gingiva Sebagai Kandidat Bahan Pasta Gigi - Alegra Trystan Mahendra Budiono (Fakultas Kedokteran Gigi, 2025)
Background: In recent decades, herbal toothpaste has gained popularity due to its safety, minimal side effects, and eco-friendliness. However, many herbal formulations still present limitations, including low remineralization capacity, insufficient antibacterial efficacy compared to synthetic agents, and inadequate abrasive properties for effective plaque removal. Gourami fish scales (Osphronemus gouramy), rich in bioactive compounds such as type I collagen, calcium, and phosphate, offer potential for tissue regeneration and tooth remineralization. Prior to their use in toothpaste formulations, it is essential to evaluate their cytotoxicity on gingival fibroblasts, which play a critical role in maintaining oral soft tissue health. Objective: This study aimed to evaluate the cytotoxicity of nanoparticle-formulated gourami fish scale extract on human gingival fibroblast cells using the MTT assay to assess its safety and potential as a natural active ingredient in toothpaste formulations. Methods: A total of 24 samples were divided into eight groups: six treatment groups (P1–P6) exposed to nanoparticle extract concentrations of 15.625, 31.25, 62.5, 125, 250, and 500 µg/mL; one group treated with NaCMC 500 µg/mL (P7); and one untreated control group (P8). Cytotoxicity was evaluated using the MTT assay by measuring absorbance values as indicators of cell viability. Absorbance data were analyzed to calculate the IC₅₀ value and further examined using one-way ANOVA followed by the Games-Howell post hoc test. Results: The highest cell viability (118%) was observed at the lowest concentration (15.625 µg/mL), suggesting a stimulatory or non-cytotoxic effect. Viability remained above 70% at 31.25 µg/mL, meeting the non-cytotoxic threshold. In contrast, concentrations of 62.5 µg/mL and above resulted in significantly decreased viability, indicating a dose-dependent cytotoxic effect. The lowest viability (5.87%) was recorded at 250 µg/mL. The calculated IC₅₀ value was 49.99 µg/mL, classifying the extract as moderately cytotoxic. The NaCMC group showed no significant cytotoxicity, confirming its biocompatibility. Conclusion: Nanoparticle extract of gourami fish scales exhibited non-cytotoxic behavior at low concentrations and moderate cytotoxicity at higher levels. Its biocompatibility at ≤ 31.25 µg/mL suggests promising potential as a natural active ingredient in topical oral formulations such as herbal toothpaste. However, careful concentration control is necessary to ensure safety in future applications.
Reaploud Repository 26 Maret_agus
Keywords: cytotoxicity; gingival fibroblasts; nanoparticles; gourami fish scales; MTT assay